PENGARUH KOMPETENSI, KOMITMEN ORGANISASIONAL DAN PROFESIONALISME GURU TERHADAP KINERJA GURU (Studi PadaSekolah Al AzharSyifa Budi II Kota Pekanbaru) - Bayu Ardinata; Marzolina '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is conducted to analyze The Influence of Competence, Organizational Commitment and Teachers Professionalism on Teachers Performance (Study at Al Azhar Syifa Budi II Pekanbaru City School).There are independent variables in this research such as Competence(X1), Organizational Commitment (X2), Teachers Professionalism (X3) and Teachers Performance (Y) as dependent variabel. The population of this study were all teachers at Al Azhar Syifa Budi II Pekanbaru City School and total sample were 58 peoples. Multiple regression method are chosen for data analysis by SPSS version 21. The result of this research shows that Competence, Organizational Commitment and Teachers Professionalism both simultaneously and partially had effects with Teachers Performance at Al Azhar Syifa Budi II Pekanbaru City School. Response of all variables give a different result each other. Competence were dominant factor towards Teacher Professionalism. Test result by simultaneously test obtained Fcount ((45,593) > Ftable (2,776) that means all those 3 dependent variable had simultaneous effect to teacher performance. The expectation of this research is Al Azhar Syifa Budi II School should improve Competence, Organizational Commitment and Teachers Professionalism among teachers in order to improve Teachers prerformance.Keyword: Competence, Commitment, Professionalism and Performance